1934
DOI: 10.1002/jcp.1030050213
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of the respiration of luminous bacteria for 2, 4‐dinitrophenol

Abstract: Since the revival of interest in the biological action of 2, 4-dinitrophenol through the work of Cutting and Tainter ( '32) and their associates, considerable information has been made available regarding the action of the drug on the animal as a whole. Comparatively few studies have been made on the action of 2, 4-dinitrophenol on unicellular organisms, although it has been pointed out that the substance in minute amounts will directly affect tissue cells, (Ehrenfest and Ronzoni, '33) and stimulate oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1935
1935
1951
1951

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The stimulating action of 2, 4-dinitrophenol on metabolism and oxygen consumption has been demonstrated for many organisms both embryonic and adult (Shoup and Kimler, 1934, luminous bacteria; Bodine and Boell, 1938, grasshopper embryos;Root and Etkin, 1937, toadfish;and others). It raises the metabolic rate of female rats (Halpern and Hendryson, 1935) but does not accelerate development in amphibian embryos (Cutting and Tainter, 1933;Dawson, 1938;Buchanan, 1938).…”
mentioning
confidence: 99%
“…The stimulating action of 2, 4-dinitrophenol on metabolism and oxygen consumption has been demonstrated for many organisms both embryonic and adult (Shoup and Kimler, 1934, luminous bacteria; Bodine and Boell, 1938, grasshopper embryos;Root and Etkin, 1937, toadfish;and others). It raises the metabolic rate of female rats (Halpern and Hendryson, 1935) but does not accelerate development in amphibian embryos (Cutting and Tainter, 1933;Dawson, 1938;Buchanan, 1938).…”
mentioning
confidence: 99%
“…The work of Shoup (1929Shoup ( , 1933Shoup ( , 1934 and of Taylor (1932Taylor ( , 1934 has shown that when respiration is inhibited by a variety of methods, e.g. K(\\, TO, excessive-dinitrophenol, lowered oxygen tension, luminescence is not affected until respiration is reduced to about 40-50 per cent of the normal, when the intensity drops off.…”
Section: Experiments With Sonic Vibrationmentioning
confidence: 99%
“…Poisons of various kinds are known to reduce the intensity of luminescence in essentially non-proliferating suspensions or masses of the bacteria (Beijeinrck, 1889, 1891Harvey, 1915;Harvey and Taylor, 1934;Hill, 1929Hill, , 1932Taylor, 1932Taylor, , 1934Taylor, , 1936Shoup, 1933;Shoup and Kimler, 1934;Korr, 1935;van Schouwenburg, 1938;van Schouwenburg and van der Burg, 1940; Johnson and Chambers, 1939;Johnson and Moore, 1941) and in some cases a stimulation of luminescence by low concentrations of the inhibitors has been noted (Taylor, 1934(Taylor, , 1936van Schouwenburg, 1938). A stimulation of growth and luminescence in broth cultures by low concentrations of urethane and of sulfanilamide (Johnson, 1942) as well as the stimulatory effects of bacteriostatic compounds, in low concentration, for various species on agar (Lamanna, 1942) lend a renewed interest to the familiar biological problem of apparent stimulations caused by low concentrations of toxic agents in general.…”
mentioning
confidence: 99%